Qualidade do ar e risco à saúde durante o ano atípico de 2020 (Fortaleza, CE) - Santos, Rafael Pereira dos (2022)
Air pollution is one of the greatest environmental threats to human health, in addition to posing risks to the economy and the environment, thus constituting a sustainability problem and being, therefore, directly mentioned in the Sustainable Development Goals (SDGs). This work aimed to evaluate the air quality in a region of Fortaleza, a highly urbanized city, observing the levels of pollutants, the daily and seasonal variations, the air quality index, the influence of traffic and meteorological parameters and possible risks to the population health during the atypical year 2020. Data from the six legislated air pollutants CO, SO2, NO2, O3 and particles (PM10 and PM2.5) and from NO were analyzed. The formation of 3 periods with significantly different pollution levels was observed: “rainy period without pandemic (PCs/p)” (February and March), “rainy period with pandemic (PCc/p)” (April to June) and “dry period with pandemic (PSc/p)” (July to August). NOx (NO + NO2) were more concentrated in the rainy season. O3 and particulate matter were more concentrated in the dry period. CO and SO2 did not show significant seasonal variations. The daily profiles showed the influence of vehicular traffic and solar radiation on pollutant concentrations. None of the pollutants exceeded national air quality standards, however, the 24-hour concentration of NO2 exceeded the World Health Organization (WHO) standard by one day. On that day, the air quality was classified as moderate by the air quality index. The other days showed good air quality. The annual concentration of PM10 exceeded the WHO standard.